Comparing learners' knowledge, behaviors, and attitudes between two instructional modes of computer programming in secondary education - Dan Sun; Fan Ouyang; Yan Li; Caifeng Zhu (SpringerOpen, 2021)
Abstract Background Unplugged programming is proved to be an effective means to foster the learner-centered programming learning. In addition to the final tests, learners' programming knowledge, skills, and capacities are primarily demonstrated throughout the programming process, particularly in the situation when they encounter challenges and problems. However, few studies examine how learners engage in the programming processes and to what extent unplugged programming fosters learning. This research used a quasi-experimental design to investigate two instructional modes in China's secondary education, namely, the instructor-directed lecturing and the learner-centered unplugged programming. Based on an analytical framework, this research used mixed methods to compare learners' knowledge, behaviors, and attitudes under these two instructional modes. Results The research results revealed discrepancies between two instructional modes. First, learners in the unplugged programming class achieved significantly higher scores on the programming knowledge assessment, compared to learners in the traditional lecturing class. Second, compared to the traditional lecturing class, learners in the unplugged programming class had higher test scores of the computational thinking skills, particularly on the cooperativity dimension. Next, discrepancies of in-class behaviors showed that learners in the unplugged programming class had frequent behaviors of listening to the instructor's instructions and discussing with peers, while learners in the instructor-directed class had frequent behaviors of listening to instructor, taking notes, and irrelevant activities. Learners' self-reported attitudes in the unplugged programming indicated a higher level of confidence than learners in the traditional lecturing class. Overall, this research revealed that the learner-centered unplugged programming had potential to improve learners' programming knowledge, behaviors, and attitudes compared to the traditional instructor-directed lecturing of programming. Conclusions As a feasible and easy-to-use instructional activity in computer science education, unplugged programming is encouraged to be integrated in formal education to increase learners' programming interests, motivations, and qualities. This quasi-experimental research compared learners' programming knowledge, behaviors, and attitudes under two instructional modes. The results revealed critical discrepancies between two instructional modes on learners' knowledge gains, in-class behaviors, and changes of attitudes towards programming. Pedagogical and analytical implications were provided for future instructional design and learning analytics of computer programming education.